Activating Calcium-Sensing Receptor Mutations: Prospects for Future Treatment with Calcilytics - Mayr, Bernhard; Glaudo, Markus; Schöfl, Christof (Trends in Endocrinology and Metabolism, 2016)
Activating mutations of the G protein-coupled receptor, calcium-sensing receptor (CaSR), cause autosomal dominant hypocalcemia and Bartter syndrome type 5. These mutations lower the set-point for extracellular calcium sensing, thereby causing decreased parathyroid hormone secretion and disturbed renal calcium handling with hypercalciuria. Available therapies increase serum calcium levels but raise the risk of complications in affected patients. Symptom relief and the prevention of adverse outcome is currently very difficult to achieve. Calcilytics act as CaSR antagonists that attenuate its activity, thereby correcting the molecular defect of activating CaSR proteins in vitro and elevating serum calcium in mice and humans in vivo, and have emerged as the most promising therapeutics for the treatment of these rare and difficult to treat diseases.
EVALuna2:2214

A group of cationic amphiphilic drugs activates MRGPRX2 and induces scratching behavior in mice - Wolf, Katharina; Kühn, Helen; Boehm, Felicitas; Gebhardt, Lisa; Glaudo, Markus; Agelopoulos, Konstantin; Ständer, Sonja; Ectors, Philipp; Zahn, Dirk; Riedel, Yvonne K.; Thimm, Dominik; Müller, Christa E.; et al. (Journal of Allergy and Clinical Immunology, 2021)
Background: Mas gene–related G protein–coupled receptors (MRGPRs) are a G protein–coupled receptor family responsive to various exogenous and endogenous agonists, playing a fundamental role in pain and itch sensation. The primate-specific family member MRGPRX2 and its murine orthologue MRGPRB2 are expressed by mast cells mediating IgE-independent signaling and pseudoallergic drug reactions. Objectives: Our aim was to increase knowledge about the function and regulation of MRGPRX2/MRGPRB2, which is of major importance in prevention of drug hypersensitivity reactions and drug-induced pruritus. Methods: To identify novel MRGPR (ant)agonists, we screened a library of pharmacologically active compounds by utilizing a high-throughput calcium mobilization assay. The identified hit compounds were analyzed for their pseudoallergic and pruritogenic effects in mice and human. Results: We found a class of commonly used drugs activating MRGPRX2 that, to a large extent, consists of antidepressants, antiallergic drugs, and antipsychotics. Three-dimensional pharmacophore modeling revealed structural similarities of the identified agonists, classifying them as cationic amphiphilic drugs. Mast cell activation was investigated by using the 3 representatively selected antidepressants clomipramine, paroxetine, and desipramine. Indeed, we were able to show a concentration-dependent activation and MRGPRX2-dependent degranulation of the human mast cell line LAD2 (Laboratory of Allergic Diseases-2). Furthermore, clomipramine, paroxetine, and desipramine were able to induce degranulation of human skin and murine peritoneal mast cells. These substances elicited dose-dependent scratching behavior following intradermal injection into C57BL/6 mice but less so in MRGPRB2-mutant mice, as well as wheal-and-flare reactions following intradermal injections in humans. Conclusion: Our results contribute to the characterization of structure-activity relationships and functionality of MRGPRX2 ligands and facilitate prediction of adverse reactions such as drug-induced pruritus to prevent severe drug hypersensitivity reactions.
CRIS-Team Scopus Importer:2021-04-19
Keywords: (drug-induced) pruritus; Mas gene–related G protein–coupled receptors; mast cells; pseudoallergic drug reactions

Bile salt subspecies activate MRGX4 expressed on sensory neurons and cause itching in humans - Wolf, Katharina; Kühn, Helen; Leibl, Victoria; Gebhardt, Lisa; Glaudo, Markus; Reeh, Peter; Fischer, Michael J. M.; Neurath, Markus; Namer, Barbara; Kremer, Andreas (HEPATOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-25

Heterozygous inactivating CaSR mutations causing neonatal hyperparathyroidism: function, inheritance and phenotype - Glaudo, Markus; Letz, Saskia; Quinkler, Marcus; Bogner, Ulrich; Elbelt, Ulf; Strasburger, Christian J.; Schnabel, Dirk; Lankes, Erwin; Scheel, Sandra; Feldkamp, Joachim; Haag, Christine; Schulze, Egbert; et al. (European Journal of Endocrinology, 2016)
Homozygous inactivating mutations of the calcium-sensing receptor (CaSR) lead to neonatal severe hyperparathyroidism (NSHPT), whereas heterozygous inactivating mutations result in familial hypocalciuric hypercalcemia (FHH). It is unknown why in some cases heterozygous CaSR mutations cause neonatal hyperparathyroidism (NHPT) clinically similar to NSHPT but with only moderately elevated serum calcium.A literature survey was conducted to identify patients with heterozygous CaSR mutations and NHPT. The common NHPT CaSR mutants R185Q and R227L were compared with 15 mutants causing only FHH in the heterozygous state. We studied in vitro calcium signaling including the functional consequences of co-expression of mutant and wild-type (wt) CaSR, patients' phenotype, age of disease manifestation and mode of inheritance.All inactivating CaSR mutants impaired calcium signaling of wt-CaSR regardless of the patients' clinical phenotype. The absolute intracellular calcium signaling response to physiologic extracellular calcium concentrations in vitro showed a high correlation with patients' serum calcium concentrations in vivo, which is similar in NHPT and FHH patients with the same genotype. Pedigrees of FHH families revealed that paternal inheritance per se does not necessarily lead to NHPT but may only cause FHH.There is a significant correlation between in vitro functional impairment of the CaSR at physiologic calcium concentrations and the severity of alterations in calcium homeostasis in patients. Whether a particular genotype leads to NHPT or FHH appears to depend on additional predisposing genetic or environmental factors. An individual therapeutic approach appears to be warranted for NHPT patients.
EVALuna2:2211

Identification of novel MRGX2-agonists triggering mast cell degranulation and potentially mediating drug-induced pruritus - Kühn, Helen; Wolf, Katharina; Boehm, F.; Glaudo, Markus; Gebhardt, Lisa; Ectors, Philipp; Agelopoulos, K.; Zahn, Dirk; Staender, S.; Kremer, Andreas (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

The G protein-coupled receptor MRGX4 is a novel receptor for bile salts expressed on sensory neurons - Wolf, Katharina; Kühn, Helen; Leibl, Victoria; Gebhardt, Lisa; Glaudo, Markus; Reeh, Peter; Fischer, Michael J. M.; Neurath, Markus; Namer, Barbara; Kremer, Andreas (SWISS MEDICAL WEEKLY, 2021)
CRIS-Team WoS Importer:2022-03-11